Invariance of reinforcement and concrete cohesion within the energy approach - Hryshchenko, Oleksandr; Kochkarev, Dmitro (Academic journal Industrial Machine Building Civil Engineering, 2025)
The work studies the problem of analytical description of reinforcement and concrete cohesion, which determines the malleability of loop joints and butt joints of prefabricated reinforced concrete structures. It also proves that existing empirical and semi-empirical models like ‘tangential stresses – displacement’ do not ensure accurate impact of common stress in reinforcement and are unable to describe the plastic stage of tenacity characterised by a transition to a quasi-uniform distribution of tangent stress along the anchoring length. The study suggests a universal analytical bond model built on a two-line chart ‘with a linear initial section where tangential stress depends on common stress in the reinforcement and a horizontal section that corresponds to the plastic stage. The level and the length of the plastic stage are determined due to the conditions for preserving the energy invariant of the bond. The writers suggest the energy criterion for the beginning of the saturation stage, understood as the equivalence state of intensity of elasto-plastic components’ energy invariants. The resulting model allows the formation of physically justified bonding diagrams suitable for use in numerical methods for calculating the compliance of joints and butt joints. .